Bruce Bronzan Press Conference re Candidate for 31st Assembly District at Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Bruce Bronzan speaking at media microphones; Channel 24 cameraman standing; Peggy Bronzan at table